Muscle mechanics - Thaller, S.; Penasso, H. (Modelling and simulation in sport and exercise, 2020)
Aspects of biomechanical modelling in general and modelling muscle mechanics in particular are discussed in this chapter. Three goals are highlighted. First, models relying on movement-independent parameters are derived. Then, methods for individual model Parameter estimation are presented. Finally, the question of sensitivity of models to their parameters is assessed. Valuable insights in the process of setting up appropriate individual models and the problems involved are given.